2021
DOI: 10.26508/lsa.202101135
|View full text |Cite
|
Sign up to set email alerts
|

UVB mutagenesis differs in Nras- and Braf-mutant mouse models of melanoma

Abstract: BRAF-mutant melanomas are more likely than NRAS-mutant melanomas to arise in anatomical locations protected from chronic sun damage. We hypothesized that this discrepancy in tumor location is a consequence of the differential sensitivity of BRAF and NRAS-mutant melanocytes to ultraviolet light (UV)-mediated carcinogenesis. We tested this hypothesis by comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 70 publications
0
27
2
Order By: Relevance
“…Moreover, some studies in rodents suggested additional factors that might contribute to melanomagenesis in similar conditions to nevogenic melanomas. For instance, BRAF mutations seem to enhance carcinogenesis resulting from UVB, meaning fewer exposures might be required for melanocyte progression into melanoma [37]. Moreover, previous studies have suggested that the susceptibility to UV might vary through the different sequence regions in the human genome depending on nucleosome structure or bound transcription factors or other factors [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies in rodents suggested additional factors that might contribute to melanomagenesis in similar conditions to nevogenic melanomas. For instance, BRAF mutations seem to enhance carcinogenesis resulting from UVB, meaning fewer exposures might be required for melanocyte progression into melanoma [37]. Moreover, previous studies have suggested that the susceptibility to UV might vary through the different sequence regions in the human genome depending on nucleosome structure or bound transcription factors or other factors [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 18 complex adjacent indel-SNV/DNV mutations in TP53 were identified, likely generated by UV radiation, with 12 in nonTSC-BCCadj NS, 5 in TSC-FAF, and 1 in TSC-NS ( Figure 10 and Supplemental Figure 10 ). These adjacent indel-SNV/DNV mutations were observed in TP53 only ( TP53 : 18 of 455 somatic mutations in skin; TSC2 : 0 of 210 somatic mutations in skin; P = 0.001, Fisher’s exact test), which suggests that these mutations occur in keratinocytes only and may be due to effects of UVB radiation, which does not reach the dermis ( 43 , 44 ). Eight of 18 (44%) indel-SNV/DNV mutations occurred within a tract of at least 3 adjacent Cs or Gs ( Supplemental Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using these models, which also carried a conditional CDKN2A knockout allele, investigators tested the potency of UVB and UVA irradiation for promoting melanoma formation. While a single dose of 4.5 kJ/m 2 UVB dramatically accelerated melanoma onset, UVA at the chosen dose of 70 kJ/m 2 produced only a modest, yet significant reduction in tumor latency as compared with control mice that were not irradiated . While the authors readily identified C to T UV signature mutations in the UVB-induced melanomas, they were not able to identify a specific signature for UVA-induced tumors.…”
Section: Animal Models Of Uva Carcinogenesismentioning
confidence: 95%
“…While a single dose of 4.5 kJ/m 2 UVB dramatically accelerated melanoma onset, UVA at the chosen dose of 70 kJ/m 2 produced only a modest, yet significant reduction in tumor latency as compared with control mice that were not irradiated. 31 While the authors readily identified C to T UV signature mutations in the UVB-induced melanomas, they were not able to identify a specific signature for UVA-induced tumors. In these very sensitive mouse models, a substantial fraction of the mice developed melanomas even in the absence of radiation, making it more difficult to identify specific UV radiation-induced changes.…”
Section: Animal Models Of Uva Carcinogenesismentioning
confidence: 97%